2015
DOI: 10.1097/mbc.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of Glanzmann's thrombasthenia with hereditary haemorrhagic telengiectasia in a man with gastrointestinal bleeding

Abstract: Here we report a case of a 57-year-old man referred to our hospital with weakness, lethargy, melena, and rectorrhalgia. His physical examination and past medical history showed gingival bleeding, several episodes of epistaxis and post-surgery bleeding. Primary laboratory evaluation revealed only anaemia. Gastrointestinal findings including upper endoscopy and colonoscopy documented normal status, but balloon endoscopy illustrated telengiectasia-like lesions in the mid-jejunum. The case was suspected to be haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…9 Because the clinical features of GT involving digestive tract hemorrhage are similar to those of bleeding caused by common gastrointestinal diseases, GT tends to be misdiagnosed. 10 Previous studies have shown that upper gastrointestinal bleeding occurs intermittently and that the amount of bleeding can become massive and difficult to control, similar to our case. Furthermore, patients with GT who develop spontaneous gastrointestinal hemorrhage often also have gastrointestinal diseases such as gastroduodenal ulcers, alimentary tract polyps, or Helicobacter pylori infection.…”
Section: Discussionsupporting
confidence: 85%
“…9 Because the clinical features of GT involving digestive tract hemorrhage are similar to those of bleeding caused by common gastrointestinal diseases, GT tends to be misdiagnosed. 10 Previous studies have shown that upper gastrointestinal bleeding occurs intermittently and that the amount of bleeding can become massive and difficult to control, similar to our case. Furthermore, patients with GT who develop spontaneous gastrointestinal hemorrhage often also have gastrointestinal diseases such as gastroduodenal ulcers, alimentary tract polyps, or Helicobacter pylori infection.…”
Section: Discussionsupporting
confidence: 85%
“…In patients with GT, bleeding occasionally improves with age [8]. Because the clinical signs of GT, which involve bleeding from the digestive tract, resemble those of bleeding caused by common gastrointestinal disorders, GT is frequently undiagnosed [9]. According to earlier research, upper and lower gastrointestinal bleeding can be enormous and challenging to manage, as it occurred intermittently in our case.…”
Section: Discussionmentioning
confidence: 61%